Chronic Administration of DEN and 2-AAF for 13 and 18 weeks in Wistar Rats Leads to Progress of Hepatocarcinogenesis - Jaime Sánchez-Meza; Marina Campos-Valdez; José A. Domíngez-Rosales; Juliana M. Godínez-Rubí; Sarai C. Rodríguez-Reyes; Erika Matínez-López; Adriana M. Salazar-Montes; Carmen M. Gurrola Díaz; Manuel A. Castro-García; Guillermo M. Zúñiga-González; Laura V. Sánchez Orozco (Annals of Hepatology)
Introduction and Objectives: Induction of hepatocellular carcinoma by administration of the agents diethylnitrosamine (DEN) and N-(2-Fluorenyl) acetamide (2-AAF) in murine animals, is a model to study liver cancer. The objective was to evaluate the alterations triggered by the chronic administration of DEN and 2-AAF during 13 and 18 weeks (wks.) in Wistar rats. Materials and Patients: Male Wistar rats (180-200 g) were organized in groups: a) Control 18 wks. (18-wk Ctl; n=6); b) Damage 18 wks. (18-wk Dmg; n=8), c) Control 13 weeks. (13-wk Ctl; n=5), and d) Damage 13 wks. (13-wk Dmg; n=6). The 13- and 18-wk Dmg groups were weekly treated with i.p DEN (50 mg/Kg) on day one and with i.g. 2-AAF (25 mg/Kg) on day three; the treatment (Tx) was maintained over 13 and 18 weeks, respectively. Then, livers and serum were collected for histological, serum biochemistry, and gene expression analyses. Statistical test Student's t-tests or Kruskal-Wallis and Mann-Whitney U were performed using the software GraphPad Prism version 8. A p value < 0.05 was considered significant. Results: The rat's survival decreased to 62.5% with the Dmg Tx for the 18-wk Dmg group at the tenth week, but when the 13-wk Dmg group was included, the survival increased to 78.5% (n= 14) until the thirteenth week. Dmg Tx tended to decrease the animal's weight and induced changes in the liver tissue (paler coloration, differentiated nodules, and hepatomegaly; to a lesser degree in the 13-wk Dmg group). Heterogeneity in the damage severity was detected among the animals of both groups, which was also found at the histological level, where there were clear signals of loss of normal hepatocyte architecture, lobular structure disorder, atypical cell enhancement, and accumulation of collagen. Probable lung metastasis was recognized in the 18-wk Dmg group (indicated by macroscopic and histological alterations). In the Dmg groups, the levels of ALT, AST, ALKP, GGT, and total proteins in serum were significantly altered; as well as CAT, SOD, COL1A, and TGFB1 expression were significantly different. In addition, IL6 was also increased in the 18-wk Dmg group. Conclusions: Dmg Tx during 13 wks. is sufficient to induce significant alterations and the 18-wk Tx exhibited possible lung metastasis. The heterogeneity in this model may be seen as a disadvantage; yet, this may be taken as a depiction of the heterogeneity found in liver cancer patients in real life.